Antimicrobial activity of traditional wines (Sopi and Moke) against Salmonella sp. and Escherichia coli - Detha, Annytha Ina Rohi; Datta, Frans Umbu (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Sopi and Moke are two traditional wines in Indonesia. The present study aimed at investigating the antimicrobial effects of Sopi and Moke as compared to other commercial disinfectants. Materials and methods: The alcohol level and pH of the traditional wines (Sopi and Moke) were determined by alcohol meter and pH meter, respectively. The susceptibility test was perfomed to determine the antimicrobial activity of Sopi against Escherichia coli which was isolated from cattle, and the activity of Moke was tested against Salmonella sp. which was a local isolate of poultry. Results: In susceptibility test, Sopi showed 17.5 mm in zone of inhibition against E. coli, while Formades®, a commercial disinfectant showed 16 mm of zone of inhibition against the same bacteria. Moke showed 17.5 mm inhibition zone against Salmonella sp., whereas Antisep®, a commercial disinfectant had 28 mm of inhibition zone against the same isolate. Conclusion: The results indicate that Sopi and Moke have antimicrobial effects on E. coli and Salmonella sp., respectively. The findings of this study suggest that Sopi and Moke can be used as potential antimicrobial agents. http://doi.org/10.5455/javar.2016.c166